Investigating concentrations and sources of polycyclic aromatic hydrocarbons in South and Central Texas bays and estuaries along the Gulf of Mexico, USA - Lloyd, Jack; Lu, Kaijun; Liu, Zhanfei (Frontiers in Marine Science, 2024)
Polycyclic aromatic hydrocarbons (PAHs) are among the most widespread organic contaminants in the environment, and anthropogenic activities can produce PAHs through a variety of pyrogenic or petrogenic means. Knowing the concentrations and sources of PAHs helps evaluate ecosystem health and manage natural resources. In this study, 16 US Environmental Protection Agency priority PAHs were analyzed in water and sediment samples collected from September 2021 to September 2023 in four bay systems along the south and central Texas coast, which are a hotpot of crude oil transportation in the United States. Our results indicated that the total concentration of PAHs ranged from 1.9 to 8.3 ng/mL in surface waters (< 0.5 m) and from 520 to 1257 ng/g in surface sediments (top 5 cm). Grain size analysis revealed that the sediment was dominated by silt (4 - 63 μm), followed by clay (< 4 μm) and sand (> 63 μm) fractions. Both organic carbon and clay content were shown to play a significant role in controlling the PAH content in sediments. Diagnostic ratios indicated that PAHs were primarily sourced via pyrolytic processes, such as the combustion of fossil fuels. Additional sampling at Port Bay, a shallow, secondary bay in the Mission-Aransas National Estuarine Research Reserve, implicated a strong role of resuspension in the distribution and composition of PAHs in the bay systems studied. Overall, these data offer insights into the concentration levels and sources of PAHs in this key region housing oil production and transportation in the United States.